The Interplay of Creativity, Imagination, Personality Traits, and Academic Performance. (March 2015) - Liang, Chaoyun; Lin, Wei-Sheng
Three separate studies were conducted to examine the combined effects of creativity, imagination, and personality traits on the academic performance of design students. Both parallel analysis and exploratory factor analysis were conducted in Study 1 to determine the appropriate structure of the Creativity Capability Scale in a sample of 148 university students. A two-factor structure, with explained variables of 50.02%, identified originality and flexibility dimensions of creativity. A confirmatory factor analysis was conducted in Study 2 to confirm the established structure of the Creativity Capability Scale in a sample of 436 university design students. Additionally, we also confirmed the structures of the Imaginative Capability Scale and the Big-Five Mini-Markers using the same sample. The analyses of composite reliability and construct validity gave good support to all the scales employed in this study. Study 3 then tested the combined effects on academic performance in a sample of 429 design students. Student performance was measured with grade point average. The hypothesis of Study 3—that conceiving imagination played a mediator role between creativity/imagination/personality and academic performance—was partially supported. The data showed that flexibility had the strongest indirect effect on academic performance, followed by conscientiousness, initiating imagination, transforming imagination, and extroversion .